Penerapan Metode Authentic Teaching Untuk Meningkatkan Hasil Belajar Fisika Siswa Kelas IX SMAN 14 Pekanabaru - Mahdalena Mahdalena (LPPM Universitas Pahlawan Tuanku Tambusai, 2015)
The purpose of research to improve student learning outcomes using Demonstration in physics class IX SMAN 14 Pekanabru 2014/2015. The research was conducted from October to December 2014 with a class IX student research subjects totaling 30 people. The results of this study were obtained by the procedure of collecting and processing the data as needed in order to improve student learning outcomes, in prasiklus obtained average value of 50.0 with 50% mastery, in cycle 1 learning outcome was obtained with an average value of 67.7 with the thoroughness 80%, and in the second cycle in the improvement of learning the average value of 78.0 with 90% mastery. It can be concluded that the